Sujeto y subjetividad en la mente extensa - Broncano, Fernando (Revista de Filosofía, 2007)
In this paper we aim to defend a version of the thesis of “extended mind” against the criticism of some authors that consider that the “extracraneal” devices cannott acomplish the requirements that the components of mental processes must meet. We propose a quality of integration as a criterion to be a mental process, and we consider that, in some situations, external devices can be considered as meeting this criterion.
Keywords: Extended mind; Subjectivity; Mental processes; Unity of mind